Gambaran Epidemiologi Peningkatan Kasus Chikungunya di Desa Kajongan Kecamatan Bojongsari Kabupaten Purbalingga - Nova Pramestuti; Ihda Zuyina Ratna Sari; Endang Setiyani; Ulfah Farida Trisnawati; Eva Lestari; Adil Ustiawan (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2021)
Purbalingga is one of the chikungunya endemic districts which have cases increased until April in 2021 as many as 512 cases from the previous 116 cases in 2020. One of the areas of the increasing case occurred in Kajongan Village, Bojongsari Subdistrict. This study aims were to describe chikungunya cases, identify sources of transmission, and risk factors for increased chikungunya cases. A case-control design was performed in Kajongan Village in March 2021. The sample consisted of 36 cases and 36 controls. Cases are patients with suspected chikungunya, controls are people who are not chikungunya suspects who live close to the suspected case. Data was collected by blood specimen collection, larvae survey, interviews and examination using Reverse Transcriptase-Polymerase Chain Reaction. The results showed that the peak of case transmission occurred in the fourth week of February 2021. The main symptoms are fever and joint pain. Of the 21 blood samples examined, 19 (90.5%) tested positive for Chikungunya virus. Of the 9 pools Aedes sp. analyzed, 1 pool tested also positive Chikungunya virus. Chi-square analysis showed that the presence of larvae in container (p-value=0.03; OR=3.5; 95% CI=0.953-24.746) and mosquito nest eradication has not carried out routinely (p-value=0.04; OR=4.8; 95% CI=0.953-24.746) have been identified as a potential risk factor. The increasing of chikungunya cases in Kajongan Village was a local transmission supported by Chikungunya virus was detected in mosquitoes.